PEMBENTUKAN KATA SECARA DERIVASIONAL DALAM BAHASA JEPANG (Suatu Kajian Morfologi) - Reny Wiyatasari (IZUMI, 2013)
Abstract Derivation is the word formation process that produce new morphems. As agglutinating language, Japanese has many kinds of affixes that have important role in lexical morphology. Those affixes are included as derivational affixes because when attached on an independent morphem (自由形態素), they show two characteristics at least. First, produce a word (語) that has different part of speech with the independent morphem (自由形態素).  Second, produce a word (語) that has same part of speech with the independent morphem (自由形態素) but differ in lexical meaning. This paper discussed how those affixes that included as derivational affixes take apart in the derivational word formation process in Japanese. Keywords : derivation, agglutinating language, lexical morphology, derivational affixes, independent morphem